Hydrothermal Synthesis of 3D Copper(II)‐Organic Frameworks: In situ Formation of 3‐Hydroxopyrazine‐2‐carboxylate from 3‐Aminopyrazine‐2‐carboxylic Acid. Issue 12 (15th August 2013) - Dehghanpour, Saeed; Jahani, Khadijeh; Mahmoudi, Ali; Babakhodaverdi, Mogtaba; Tabatabaei, Robabehsadat; Notash, Behrouz
Abstract Abstract. The metal organic framework, [Cu5(C5H2N2O3)4(H2O)4(NO3)2·10H2O]n (1), was synthesized by a hydrothermal reaction via copper nitrate and in situ generated 3‐hydroxopyrazine‐2‐carboxylate from 3‐aminopyrazine‐2‐carboxylic acid. Compound 1 was characterized by elemental analysis, infrared spectroscopy, TG analysis, and single‐crystal X‐ray diffraction. It has a 3D structure constructed from Cu2+ cations, bridging NO3– anions, and 3‐hydroxopyrazine‐2‐carboxylate units. The NO3– anions act as μ2‐bridging ligand and the 3‐hydroxopyrazine‐2‐carboxylate units coordinate pentadentately through the two oxygen atoms of their carboxylate group, the oxygen atom of the hydroxyl group and two nitrogen atoms. The ligands link the CuII ions to form trinuclear units. These are further connected to form a novel 3D MOF, with a novel 4‐nodal 3, 3, 3, 4‐connected net topology of an unprecedented point (Schläfli) symbol (6.7.9)(64.8.9)(7.102)(72.10).